Review of the U.S. Navy Environmental Health Center's health-hazard assessment process (National Academy Press, 2000)
A large number of chemicals are used on land at shore facilities, in the air in combat and reconnaissance aircraft, on seas around the world in surface vessels, and in submarine vessels by the Navy and Marine Corps. Although the chemicals used are for the large part harmless, there is a significant amount of chemicals in use that can be health hazards during specific exposure circumstances. The Navy Environmental Health Center (NEHC) is primarily tasked with assessing these hazards. The NEHC completes its tasks by reviewing toxicological and related data and preparing health-hazard assessments (HHAs) for the different chemicals. Since the NEHC is continually asked to develop these HHAs, the National Research Council (NRC) was asked to assess independently the validity and effectiveness of NEHC's HHA process, in order to determine whether the process as implemented provides the Navy with the best, comprehensive, and defensible evaluations of health hazards and to identify any elements that might require improvement. The task was assigned to the Board on Environmental Studies and Toxicology's Committee on Toxicology's (COT's) Subcommittee on Toxicological hazard and Risk Assessment. Review of the U.S. Navy Environmental Health Center's Health-Hazard Assessment Process presents the subcommittee's report. The report is the work of expertise in general toxicology, inhalation toxicology, epidemiology, neurotoxicology, immunotoxicology, reproductive and developmental toxicology, pharmacology, medicine, risk assessment, and biostatistics. It is based on its review of documents provided by NEHC, presentations by NEHC personnel, and site visits to NEHC in Norfolk, Virginia and an aircraft carrier in San Diego, California.